PRAKTIK KEPEMIMPINAN TRANSFORMASIONAL DALAM MENGELOLA PRODUKTIVITAS TIM PADA START-UP DIGITAL DI INDONESIA - Moh. Sutoro (Yayasan Education and Social Center, 2026)
This study aims to explore the practice of transformational leadership in managing team productivity in digital start-ups in Indonesia. A qualitative approach was employed, using semi-structured interviews, participatory observation, and organizational documentation for data collection. Data analysis was conducted using NVivo to identify themes, patterns, and meanings of team interactions and the influence of transformational leadership dimensions on productivity. The results indicate that the four dimensions of transformational leadership Inspirational Motivation, Idealized Influence, Intellectual Stimulation, and Individualized Consideration synergistically enhance motivation, creativity, collaboration, and team performance. Inspirational Motivation fosters shared vision understanding, Idealized Influence builds professional role modeling, Intellectual Stimulation promotes innovation, and Individualized Consideration addresses individual needs. These findings confirm that transformational leadership is an effective strategy for maintaining productivity and innovation in the dynamic environment of digital start-ups. This study provides both theoretical and practical contributions to leadership development and team management in digital organizations in Indonesia.